Adverse effects of GHB-induced coma on long-term memory and related brain function. (1st September 2018) - Raposo Pereira, Filipa; McMaster, Minni T.B.; Polderman, Nikki; de Vries, Yvon D.A.T.; van den Brink, Wim; van Wingen, Guido A.
Highlights: GHB-induced comas are associated with alterations of long-term memory network. GHB-Coma group performed worse on the verbal memory test. GHB-Coma group showed lower hippocampus activity while performing the memory task. GHB-Coma group showed lower lingual gyrus activity while performing the memory task. GHB-Coma group showed reduced hippocampal functional connectivity with the left STC. Abstract: Background: Gamma-Hydroxybutyric acid (GHB) is a drug of abuse associated with increasing numbers of GHB-dependent patients and emergency attendances often related to GHB-induced coma. Animal studies suggest that GHB induces oxidative stress in the hippocampus, resulting in memory impairments. However, the consequences of chronic GHB use and GHB-induced coma on human brain function and cognition are unknown. Methods: We recruited 27 GHB users with ≥4 GHB-induced comas (GHB-Coma), 27 GHB users without a coma (GHB-NoComa), and 27 polydrug users who never used GHB (No-GHB). Participants completed verbal and spatial memory tests and an associative memory encoding task during functional magnetic resonance imaging (fMRI) to probe hippocampus functioning. Results: The GHB-Coma group showed a lower premorbid IQ (p = 0.006) and performed worse on the verbal memory test (p = 0.017) compared to the GHB-NoComa group, despite exhibiting similar levels of education. Compared with the other two groups, the GHB-Coma group showed lower left hippocampus (pSVC  = 0.044) and left lingual gyrus (pFWE  = 0.017) activity, and a trend for lower hippocampal functional connectivity with the left superior temporal cortex during performance of the associative memory encoding task (pFWE  = 0.063). No significant differences were observed between the GHB-NoComa group and the No-GHB group. Conclusions: These results suggest that multiple GHB-induced comas, but not the use of GHB per se, are associated with alterations of memory performance and memory-related brain, although no causal link can be inferred from this cross-sectional study. The results highlight the need for public awareness to minimize the negative health consequences of recreational GHB use, in particular when related with GHB-induced comas.